CT-Based Measurements of the Sphenoid Trigone in Different Sex and Race. Issue 2 (March 2015) - Lefebvre, Daniel R.; Yoon, Michael K.
<x xml:space="preserve">Abstract</x> Purpose: In thyroid orbitopathy, surgical treatment of exophthalmos and compressive optic neuropathy is orbital decompression. Deep lateral wall decompression has been advocated alone or combined with the medial wall for a "balanced" decompression. The degree of lateral decompression is dependent on the volume of the sphenoid trigone comprising the deep lateral orbital wall. This study aims to compare the volume of the trigone in various races in men and women. Methods: After Institutional Review Board approval, patients with normal sinus CT scans (Siemens Somatom 40-slice) were retrospectively reviewed. Inclusion criteria were men and women aged 30 to 60 years, no orbital disease or surgery, normal orbital CT scans, and self-reported race (Asian, black/African American, white). Scans were measured with imaging software (Synapse, Fujifilm USA). The superior and inferior extents of the measured trigone were the superior and inferior orbital fissures, respectively. In the axial CT plane, the areas of each slice of the right and left trigone were manually outlined with the software and volume subsequently calculated based on the slice thickness (2 mm). Comparisons between groups were made via repeated measures analysis of variance. Results: One hundred twenty subjects were included, 20 from each subgroup, yielding 240 measured orbits. The overall volume of the sphenoid trigone for all groups combined was 1.53 cm3 (standard deviation 0.72 cm3). Mean male volume was significantly larger than mean female volume (1.71 ± 0.83 cm3 vs. 1.35 ± 0.55 cm3; p = 0.004). Average left side volume was larger than paired right side volume (1.58 ± 0.74 cm3 vs. 1.49 ± 0.71 cm3; p = 0.02). There were no significant differences in average volumes between races (p = 0.17). Conclusions: The mean sphenoid trigone volume was larger in men than in women. There were no significant differences in volume between racial groups. The data showed significant interindividual and intraindividual variability. When analyzing these data for the purposes of orbital decompression, planning should be based on each side of each patient, as the expected degree of lateral decompression may vary greatly.